Program Crafting Letters, Shaping Meaning: Innovation in Kitabah Learning - Hasan Abidin; Ibnu Mas’ud Lutfi; Moch. Sholich (Al-Qalam Institute, 2024)
This study focuses on evaluating the effectiveness of the Kitabah learning program in improving the ability to write Arabic letters among students at TPQ Ulul Albab, Blaru Badas, Kediri. The main objective of this study is to identify the extent to which the Kitabah learning method can help students overcome difficulties in writing Hijaiyah letters and correctly constructing Arabic sentences. Participatory Action Research (PAR) is the research method used, which involves active participation from TPQ administrators, students, and the surrounding community in every study stage. Data were collected through direct observation, in-depth interviews, and focus group discussions, then analyzed using the Miles and Huberman data analysis model, which includes data reduction, data presentation, and conclusion. The study results indicate that the Kitabah learning program significantly improves students' ability to write Arabic letters at various grade levels. Students show improvements in the speed and accuracy of writing Hijaiyah letters, constructing sentences, using c, and correcting Arabic punctuation. This study implies that a systematic and comprehensive approach to Kitabah learning can be an effective model to be implemented in other TPQs to improve the quality of Arabic language learning in non-formal educational institutions. This study also underlines the importance of ongoing evaluation and intensive guidance in supporting successful language learning.